The Influence of Employer Branding and Organizational Commitment on Turnover Intention - Noviyanti, Rosa (Lentera Ilmu Nusantara, 2023)
This study aims to explore the influence of Employer Branding and organizational commitment on turnover intention in the manufacturing sector. By involving 93 respondents in this study. Through a quantitative approach, the data collection method uses a questionnaire with simple random sampling. Questionnaire data was analyzed using Smart PLS software. The results of the analysis show that Employer Branding has a significant positive impact on reducing the intention to move among manufacturing employees. Similarly, high levels of organizational commitment are associated with low turnover intentions, providing evidence that employees who feel emotionally and normatively attached to the company tend to stay in it. This study contributes to the understanding of the factors that influence the decision of employees in the manufacturing sector to consider moving. The implication of these findings is the importance of building a positive corporate image and strengthening the emotional and normative bonds between employees and the organization. This research confirms that an effective Employer Branding strategy and increased organizational commitment can play an important role in reducing turnover intention.